3D morphology reconstruction of rock joints from 2D profile measurement by a profilograph. (15th November 2022) - Liu, Songlin; Wang, Changshuo; Du, Shigui; Yong, Rui; Yu, Yang; Sun, Hongyue
Highlights: A methodology is proposed to reconstruct the 3D morphology of rock joints using 2D profiles measured by a profilograph. The optimal spatial interpolation method and the appropriate profile interval for the proposed methodology are determined. Influences of the joint mechanical parameters, joint roughness level, and joint size on the appropriate profile interval are ascertained. The performance of the proposed methodology is validated from experimental and theoretical perspectives. Relative errors of the test cases are within the engineering permissible error range, and more than 92% of the test cases are associated with an error less than 5%. Abstract: Rock mass stability is closely related to the shear strength of rock joints. Measuring the joint surface morphology is of vital importance for evaluating the shear strength of rock joints. Although non-contact measurement methods such as laser scanning are advantageous in high precision, the characteristics of high purchase cost or rental fees and being susceptible to the operating environment have weakened their practicability for in-situ batch measurement of the three-dimensional (3D) morphology of joints. To facilitate the possibility of utilizing cost-effective contact-based devices to replace the non-contact ones, we proposed a methodology to reconstruct the 3D morphology of rock joints using two-dimensional (2D) joint profiles measured by contact measurement methods (e.g., a profilograph). First, through a comprehensive comparison of commonly used spatial interpolation methods, the V4 method from the Griddata function is determined as the optimal one for the proposed methodology. Then, based on the optimal spatial interpolation method, the appropriate profile interval is determined through a referential band derived in this study. Finally, the performance of the proposed methodology was validated from experimental and theoretical perspectives. Results show that the relative errors of the test cases are within the engineering permissible error range, and more than 92% of the test cases are associated with an error less than 5%. In addition, the influences of the joint mechanical parameters, joint roughness level, and joint size on the appropriate profile interval are investigated. This methodology offers a cost-effective alternative for in-situ batch measurement of joint 3D morphology in the field survey of rock joints.